Clinical evaluation of negative mNGS reports in sterile body fluids and tissues - Wang Lisha; Qian Jiao; Chen Mengyuan; Qin Jiajia; Tang Tianbin; Wang Yilan; Hu Linjie; Yu Sufei (Microbiology Spectrum, 2025)
ABSTRACT Regarding metagenomics next-generation sequencing (mNGS) negative literature, there have been much discussions about methodology; thus, we collected clinical and laboratory information for retrospective evidence-based research. We retrospectively analyzed 150 negative mNGS results of patients suspected of having aseptic body fluid infections and divided them into a plasma group, cerebrospinal fluid (CSF) group, and others group according to the sample types. Based on the final laboratory and clinical diagnoses, the diagnostic accuracy of excluding infections in the plasma, CSF, and others groups of negative mNGS results were 72.0%, 40.4%, and 30.2%, respectively. The false-negative rates of the CSF and others group were relatively high. The positive impact rates of clinical application in the plasma, CSF, and others groups were 68.0%, 40.4%, and 25.6%, respectively. Three factors, including patient department distribution, admission symptoms, and doctors' judgment of patient infection were used to analyze the reasons for uncertain negative or false-negative results in mNGS. The clinical information analysis of false-negative patients’ aims were to reduce the false-negative rate and improve the diagnostic accuracy of mNGS. On the selection of sampling timing in mNGS, within half a month after a patient develops suspected symptoms of infection, the earlier the mNGS test, the higher the true-negative rate.IMPORTANCEThere has been little research carried out on the diagnostic value of negative metagenomics next-generation sequencing (mNGS) results in clinical practice, especially for sterile body fluids. In the present study, plasma negative mNGS results showed the highest diagnostic accuracy for excluding infection. However, the cerebrospinal fluid and other mNGS false-negative rates were 59.6% and 69.8%, respectively. Our findings emphasized the role of negative mNGS results in practical clinical applications and clarified that patients, mNGS sampling time, and doctor’s decision making were the key factors for the diagnosis of clinical infections. More attention should be paid to the diagnostic role of mNGS true negatives, the analysis of clinical patterns of false negatives, and improving the diagnostic accuracy of mNGS.